2011
DOI: 10.1055/s-0030-1269907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of All-transRetinoic Acid on Sodium/Iodide Symporter and CCAAT/Enhancer-binding Protein-Homologous Protein under Condition of Endoplasmic Reticulum Stress in FRTL5 Thyroid Cells

Abstract: In thyroid cells, the effects of all- TRANS retinoic acid (ATRA) on sodium/iodide symporter (NIS) and CCAAT/enhancer-binding protein-homologous protein (CHOP) under condition of endoplasmic reticulum (ER) stress have not been evaluated. In the present study, the relationships between NIS, CHOP, and p38 MAPK, and the effects of ATRA on NIS and CHOP expression as well as on p38 MAPK activation under condition of ER stress in thyroid cells were investigated. In FRTL5 thyroid cells, NIS mRNA and protein levels dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…As shown in Fig 2A , the mRNA levels of NIS, TG and TPO were reduced by about 30 to 50% by TM at a concentration of 0.1 μg/mL (P < 0.05). This result is in agreement with earlier observations that different ER stress inducers decrease the expression of genes involved in thyroid hormone synthesis, like TG [ 10 ] and NIS [ 50 ]. At concentrations of TM ≤ 0.05 μg TM/mL, which were found to cause ER stress, no effect on expression of these genes was observed.…”
Section: Resultssupporting
confidence: 93%
“…As shown in Fig 2A , the mRNA levels of NIS, TG and TPO were reduced by about 30 to 50% by TM at a concentration of 0.1 μg/mL (P < 0.05). This result is in agreement with earlier observations that different ER stress inducers decrease the expression of genes involved in thyroid hormone synthesis, like TG [ 10 ] and NIS [ 50 ]. At concentrations of TM ≤ 0.05 μg TM/mL, which were found to cause ER stress, no effect on expression of these genes was observed.…”
Section: Resultssupporting
confidence: 93%
“…racecadotril and i.c.v. thiorphan directly inhibit an insulin-degrading enzyme in the brain, and that brain insulin acts via the vagal nerve on plasma glucose (Lee et al, 2011). The clinical findings of these intriguing observations have not been explored in patients to our knowledge.…”
Section: Studies On Central Nervous System Functionmentioning
confidence: 99%
“…A recent report indicated that RA might attenuate ER stress-induced CHOP expression by modulating the phosphorylation of p38 MAPK in FRTL5 thyroid cells 49 . However, the relationship between RA and ER stress in SCI has not been reported.…”
Section: Resultsmentioning
confidence: 99%